Vestibular Deprivation and the Development of Dendrite Bundles in the Rat - Hildegard C. Geisler; Jos IJkema-Paassen; Johan Westerga; Albert Gramsbergen (Neural Plasticity)
Motoneuronal pools of muscles that subserve postural tasks contain dendrite bundles. We investigated in the rat the development of these bundles in the pools of the long back muscles and related this to postural development. Motoneurons and their dendrites were retrogradely labeled by injecting unconjugated cholera toxin subunit B (CTB) into the muscles of 54 normal rats from birth until adulthood and into 18 rats that were vestibularly deprived from the 5th postnatal day (P5). Dendrite bundles coursing in a transverse direction already occurred at P1. From P4, the first longitudinal bundles could be observed, but the major spurt in development occurred between P6 and P9, when conspicuous bundles developed coursing in rostro-caudal and tranverse directions. This is the age when rats become able to stand freely and walk a few steps. Around P20, the dendrite bundles attained their adult characteristics. Vestibular deprivation by plugging both semicircular horizontal canals did not lead to a retarded development of dendrite bundles nor to a changed morphology. This finding is remarkable, as behavioral analysis showed a delay in postural development by about 3 days. We hypothesize that dendrite bundles in the pools of the long back muscles function to synchronize the motoneurons in different spinal cord segments.